Navigating the landscape through digital human resource management: an initiative to achieve sustainable practices - Virmani, Naveen; Sharma, Shikha; Kumar, Pranav; Luthra, Sunil; Jain, Vranda; Jagtap, Sandeep (Elsevier, 2025)
The adoption of Digital Human Resource Management (DHRM) is increasing exponentially in the present market landscape; organizations are curious to digitalize human resource practices and enhance organizational performance. The purpose of the presented research is to assess various factors impacting DHRM adoption. The presented study is grounded in social exchange theory and dynamic capability theory. The survey instrument was developed using a literature review. Data from 269 respondents was collected, and Structural Equation Modeling was used to analyze the data. The research investigated the role of DHRM in achieving organizational performance. Furthermore, the role of sustainable Human Resource Practices (SHRP) is examined as a mediating variable. Also, the impact of Employee Engagement is analyzed on organizational performance. Moreover, the role of Management Support is analyzed to assess the relationship between DHRM, SHRP, and Employee Engagement (EENG). The result indicates that external environmental factors significantly impact DHRM practices. Also, SHRP partially mediates the association between DHRM and EENG. DHRM enables professionals to analyze real-time data, allowing managers to make informed decisions. In today's globalized scenario, the emergence of DHRM concept helps to automate and streamline Human Resource (HR) tasks, including performance management, recruitment, training, and appraisal, which eventually help to attain a sustainable competitive advantage. As found in existing literature, the DHRM domain is novel, and more empirical studies must investigate crucial aspects affecting DHRM adoption. Therefore, this study focuses on bridging the identified gaps.
Keywords: 33 Built Environment and Design; 44 Human Society; 4404 Development Studies; 3302 Building; 3304 Urban and Regional Planning; 3302 Building; 3304 Urban and regional planning; 4404 Development studies; Digital Human Resource Management; Employee engagement; Management support; Organizational Performance; Human resources; Sustainable Human Resource Practices